Snapshots of Sanctuary : Self-definitions of immigrant support in Eugene, Oregon - Wuerth, Milena (re:think - a journal of creative ethnography, 2021)
Summary: Since its inception in the 1980s, the US ‘Sanctuary Movement’ has been the source of contentious political debate and academic discussion. Although originally a clergy-based effort of transnational activism, ‘sanctuary’ has since diffused beyond the bounds of any one movement or social denomination. In this ethnography, ‘sanctuary’ is examined as a term inflected in diverse, instrumental, and meaningful ways by those participating in immigrant-support groups and non-profits in Eugene, Oregon. Research was conducted over a two-month period from August through September 2019 and funded by the London School of Economics’ Summer Ethnographic Project.